Risk factors for nonpurulent leg cellulitis: a systematic review and meta‐analysis. (25th July 2017) - Quirke, M.; Ayoub, F.; McCabe, A.; Boland, F.; Smith, B.; O'Sullivan, R.; Wakai, A.
Summary: Nonpurulent cellulitis is an acute bacterial infection of the dermal and subdermal tissues that is not associated with purulent drainage, discharge or abscess. The objectives of this systematic review and meta‐analysis were to identify and appraise all controlled observational studies that have examined risk factors for the development of nonpurulent cellulitis of the leg (NPLC). A systematic literature search of electronic databases and grey literature sources was performed in July 2015. The Newcastle–Ottawa Scale (NOS) was used to assess methodological quality of included studies. Of 3059 potentially eligible studies retrieved and screened, six case–control studies were included. An increased risk of developing NPLC was associated with previous cellulitis [odds ratio (OR) 40·3, 95% confidence interval (CI) 22·6–72·0], wound (OR 19·1, 95% CI 9·1–40·0), current leg ulcers (OR 13·7, 95% CI 7·9–23·6), lymphoedema/chronic leg oedema (OR 6·8, 95% CI 3·5–13·3), excoriating skin diseases (OR 4·4, 95% CI 2·7–7·1), tinea pedis (OR 3·2, 95% CI 1·9–5·3) and body mass index > 30 kg m −2 (OR 2·4, 95% CI 1·4–4·0). Diabetes, smoking and alcohol consumption were not associated with NPLC. Although diabetics may have been underrepresented in the included studies, local risk factors appear to play a more significant role in the development of NPLC than do systemic risk factors. Clinicians should consider the treatment of modifiable risk factors including leg oedema, wounds, ulcers, areas of skin breakdown and toe‐web intertrigo while administering antibiotic treatment for NPLC. Abstract : What's already known about this topic? Nonpurulent leg cellulitis (NPLC) is a major healthcare burden even in areas where community‐associated methicillin‐resistant Staphylococcus aureus infection is endemic. Treatment of risk factors for developing NPLC may promote resolution of the infection and reduce the rate of recurrence. There is currently no published systematic review of risk factors for developing NPLC. What does this study add? A comprehensive systematic review and meta‐analysis of observational studies examining risk factors for developing leg cellulitis. Local (leg) risk factors appear to be more significant than systemic risk factors in the development of cellulitis. Previous cellulitis is highly predictive of cellulitis recurrence. Treatment of modifiable risk factors, including leg oedema, wounds, ulcers, areas of skin breakdown and toe‐web intertrigo, is likely to reduce the recurrence of cellulitis.